PENGGUNAAN MEDIA AUDIO VISUAL GERAK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM SECARA DARING DI KELAS XI TKJ SMK NEGERI 3 KOTA MALANG - Mohamad Haditia; Rosichin Mansur; Lia Nur Atiqoh Bela Dina (VICRATINA, 2022)
The background of this research problem is the difficulty of teaching if it is only with the lecture method so that it makes the learning process boring, with this the PAI teacher at SMK N 3 Malang has the initiative to use motion audio-visual media in Islamic Religious Education lessons. The formulation of the problem in this study is how to plan motion audio-visual media in online PAI learning in class XI Computer Network Engineering at SMK Negeri 3 Malang? How is the implementation of motion audio-visual media in online PAI learning in class XI Computer Network Engineering at SMK Negeri 3 Malang? How are student learning outcomes by applying motion audio-visual media in online PAI learning in class XI Computer Network Engineering at SMK Negeri 3 Malang? while the aim is to describe the planning of motion audio visual media in online PAI learning in class XI of Computer Network Engineering at SMK Negeri 3 Malang. Describes the implementation of motion audio visual media in online PAI learning in class XI Computer Network Engineering at SMK Negeri 3 Malang. Describe student learning outcomes by applying motion audio-visual media in online PAI learning in class XI Computer Network Engineering at SMK Negeri 3 Malang. This research uses a qualitative research method with the type of case study research. While the data collection techniques are observation, interviews and documentation. Data analysis techniques were carried out by collecting data, condensing data, presenting data, and drawing conclusions. Checking the validity of using Extended Observation and Triangulation data from triangulation has 3 kinds such as source triangulation, technical triangulation, and time triangulation. In this study, there were 3 research results, namely: First, planning in the planning stage of the stages carried out by the teacher before using motion audio-visual media was making lesson plans, making videos according to the learning theme and sending material to be studied online. Second, the implementation of the discussion on the implementation of audio-visual motion media in PAI learning Online In Class XI TKJ SMK N 3 Malang City, it can be concluded that the activities carried out by the teacher in the implementation process are distributing links according to the application used, praying, and displaying videos according to with learning materials. The three student learning outcomes the results of using audio-visual motion media online at SMK N 3 Malang are to encourage students to be able to follow the rapid development of technology, be able to introduce new learning media so that they can add new insights, students and students are more concentrated in learning.